Cab-Over-Engine truck cabins: A mathematical model for dynamics, driver comfort, and suspension analysis and control. (March 2023) - Lu, Yukun; Khajepour, Amir; Soltani, Amir; Wang, Yonggang; Zhen, Ran; Liu, Yegang; Li, Guoqiang
Various cabin designs have been developed for commercial vehicles to meet different driver comfort requirements. Among those configurations, the cab-over-engine (COE) is widely used because of its compact size and good road visibility. Since the engine is assembled underneath the cabin, it is required that the cabin can be entirely tilted forward in order to access the engine for inspection and maintenance. Hence, the forepart of the cabin suspension is designed to connect with the chassis frame through a linkage mechanism. The dynamic modelling of this commonly used configuration was lack of study in the literature, but it is essential for further cabin's dynamic analysis and vibration control. Considering the rapid development of the comfort-oriented cabin suspension, this study introduces a multi-body dynamic modelling approach for the COE cabin with a titling mechanism. The dynamic equations are derived based on the Lagrangian modelling method, which are then implemented in MATLAB/Simulink. Besides, a high-fidelity truck model is developed in ADAMS/Car to study the accuracy of the proposed dynamic model through co-simulation. Meanwhile, a four-point cabin model that has been widely used in past studies is used as the benchmark. The simulation results demonstrate that the proposed cabin dynamic model can accurately estimate the cabin's behaviour in vertical, roll, and pitch directions, which can be used for cabin dynamics, ride comfort, and cabin suspension control studies.